1995
DOI: 10.1093/oxfordjournals.eurheartj.a060789
|View full text |Cite
|
Sign up to set email alerts
|

Heart rate variability and inappropriate sinus tachycardia after catheter ablation of supraventricular tachycardia

Abstract: Sinus tachycardia has been reported after radiofrequency catheter ablation of supraventricular tachycardia. Frequently, these patients require beta-blocking agents for symptomatic control. The purpose of this study was to evaluate prospectively the incidence of inappropriate sinus tachycardia and heart rate variability after ablation of atrioventricular nodal reentrant tachycardia and accessory pathways. Patients undergoing ablation had 24-h ambulatory monitoring ECG (Holter) performed before the procedure, on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
30
0
5

Year Published

1999
1999
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 0 publications
1
30
0
5
Order By: Relevance
“…1-6,16 -19 In the present study, the prevalence of inappropriate sinus tachycardia was 6.7%, similar to that in previous reports regarding ablation of supraventricular tachycardias. [1][2][3]17,18 We also found decreases in SDRR, rMSSD, and HF and increases in mean and maximal sinus rate and LF/HF ratio, which indicates autonomic dysfunction, just like the findings after ablation of supraventricular tachycardias. Furthermore, no significant changes in HR and HRV were noted in our control group, which indicates autonomic dysfunction after ablation of PVs was not related to the transseptal procedure.…”
Section: Autonomic Dysfunction After Ablation Of Pvssupporting
confidence: 72%
See 2 more Smart Citations
“…1-6,16 -19 In the present study, the prevalence of inappropriate sinus tachycardia was 6.7%, similar to that in previous reports regarding ablation of supraventricular tachycardias. [1][2][3]17,18 We also found decreases in SDRR, rMSSD, and HF and increases in mean and maximal sinus rate and LF/HF ratio, which indicates autonomic dysfunction, just like the findings after ablation of supraventricular tachycardias. Furthermore, no significant changes in HR and HRV were noted in our control group, which indicates autonomic dysfunction after ablation of PVs was not related to the transseptal procedure.…”
Section: Autonomic Dysfunction After Ablation Of Pvssupporting
confidence: 72%
“…[1][2][3][4][5][6] Therefore, we performed 24-hour Holter monitoring at 1 and 6 months after ablation of PVs, respectively, to see the chronic changes in HRV. The results showed that an increase in HR and a decrease in HRV recovered at 1 month after ablation of PVs, indicating a transient dysfunction of autonomic nervous system, just as the findings after ablation of supraventricular tachycardias.…”
Section: Recovery Of Autonomic Dysfunction After Ablation Of Pvsmentioning
confidence: 99%
See 1 more Smart Citation
“…[6][7][8][9][10][11][12] Kocovic, et al 7) first described the parasympathetic damage that occurs in combination with an atrial septal RFCA during therapy for atrioventricular (AV) nodal reentrant tachycardia (AVNRT) or AV reciprocating tachycardia utilizing a septal Kent bundle, and speculated that it was due to injury to the vagal ganglia or neural fibers existing in that area. They also reported that RFCA of a left lateral Kent bundle did not cause any parasympathetic damage.…”
mentioning
confidence: 99%
“…Even if there is some discrepancy between the human and canine cardiac parasympathetic distribution, it is natural that an atrial septal RFCA would yield some vagal damage to the SA node even in human hearts. [6][7][8][9][10][11][12] Recently, RFCA application to the pulmonary veins (PVs) or in the vicinity of their ostia has become an effective strategy for treating paroxysmal atrial fibrillation (AF). [20][21][22][23][24] According to the above-mentioned neural distribution, RFCA of the right PVs could also cause vagal denervation similar to that with AVNRT therapy.…”
mentioning
confidence: 99%